City Leadership in Responding to Climate Change and Sustainable Development Issues: A Case Study of Pivot City Samarinda City - Laode Muhammad Fathun; Alfiyah Nur Rahmalia; Alya Zahra Sabira (Nusantara Innovation Journal, 2025)
This research aims to explore and identify the role of City Diplomacy in supporting Global Leadership. The argument of this thesis is that cities are global actors that are not only tasked with addressing local issues. The involvement of the City in its role of conducting city diplomacy is a form of city leadership to contribute in guarding global issues such as climate change. In this case, the involvement of Samarinda as a CRIC Pivot City in the UCLG ASPAC Programme is evidence of the city's leadership in international relations. This research uses qualitative methodology with data collection techniques of interviews, participant observation, document review. Data analysis techniques used qualitative data analysis techniques and process tracing. The result of this research is that the involvement of Samarinda City in the UCLG ASPAC CRIC programme is evidence of the importance of city involvement in international relations. This factor occurs due to economic, social, political, environmental, etc. considerations. In addition, the involvement of Samarinda City as a Pivot City is a form of commitment and leadership of the city in the global arena. In particular, Samarinda City has succeeded in becoming a city as place that prioritises and fights for the threat of climate change in Samarinda. This struggle is a form of effort to create a city that is worth living in. It then acts as an actor capable of collaborating with UCLG ASPAC to be directly involved in managing climate change issues. The leadership of Samarinda City is a tangible form of creating a sustainable city in accordance with SDGs point 11.